Stability of Varenicline Concentration in Saliva Over 21 Days at Three Storage Temperatures. Issue 2 (30th August 2021) - Novalen, Maria; Chenoweth, Meghan J; Zhao, Bin; Hawk, Larry W; Tyndale, Rachel F
Abstract: Introduction: Varenicline is the most efficacious drug for smoking cessation; saliva varenicline concentrations can be useful for the evaluation of adherence in smoking cessation trials. Saliva is a useful noninvasive matrix for mail-in specimen collection, if stable. We investigated the stability of varenicline in saliva at different storage temperatures simulating the time it takes to mail in a sample. Methods: We evaluated the concentrations of varenicline, nicotine, cotinine, 3′-hydroxycotinine, and 3′-hydroxycotinine/cotinine (3HC/COT) ratio in quality control saliva samples (and after repeated freezing and thawing), and in smokers' saliva samples, stored for up to 21 days at room temperature ( 25°C), 4°C, and −80°C. Results: In saliva quality control samples, concentrations of varenicline, nicotine, cotinine, 3′-hydroxycotinine, and 3HC/COT remained unchanged and showed little within-sample variation (CV ≤ 5.5%) for up to 21 days at the three storage temperatures; they were also not altered after three thaw-freeze cycles. In smokers' saliva, a significant main effect of storage duration, but not temperature, was observed for varenicline, cotinine, and 3′-hydroxycotinine, but not for nicotine or the 3HC/COT ratio. However, these changes were within analytical (i.e., equipment) variation resulting in little within-sample variation (CV ≤ 5.8%) for all analytes in smokers' saliva. Conclusions: Varenicline, the other analytes, and the 3HC/COT ratio remained stable in saliva during storage for 21 days at all temperatures tested and after repeated freezing and thawing with only minor changes in concentration over time. These findings support the potential use of mail-in approach for saliva samples in varenicline smoking cessation clinical trials. Implications: Assessing saliva varenicline concentrations can be useful for the evaluation of adherence in smoking cessation trials. Saliva is a noninvasive matrix suitable for mail-in specimen collection. This is the first investigation of stability of varenicline in saliva. Varenicline, nicotine, cotinine, 3′-hydroxycotinine, and 3HC/COT were stable in saliva for up to 21 days at room temperature ( 25°C), 4°C, and −80°C, supporting the use of a mail-in approach for saliva specimen in smoking cessation trials.